2002
DOI: 10.1897/1551-5028(2002)021<0480:tpfeae>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Estradiol and Ethinylestradiol Degradation in English Rivers

Abstract: Water samples were collected in spring, summer, and winter from English rivers in urban/industrial (River Aire and River Calder, Yorkshire, UK) and rural environments (River Thames, Oxfordshire, UK) to study the biodegradation potential of the key steroid estrogen 17beta-estradiol (E2) and its synthetic derivate ethinylestradiol (EE2). Microorganisms in the river water samples were capable of transforming E2 to estrone (E1) with half-lives of 0.2 to 9 d when incubated at 20 degrees C. The E1 was then further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 0 publications
9
67
0
Order By: Relevance
“…In the same experimental set up, EE2 appeared to be stable. The findings for the conversion of E2 to E1 were confirmed in experiments with river water samples, in which E2 was converted into E1 and mineralised according to first order kinetics (Jürgens et al, 2002). The findings for the conversion of E2 to E1 were confirmed in experiments with river water samples, in which E2 was converted into E1 and mineralised according to first order kinetics (Jürgens et al, 2002).…”
Section: Activated Sludge Systemsmentioning
confidence: 58%
See 2 more Smart Citations
“…In the same experimental set up, EE2 appeared to be stable. The findings for the conversion of E2 to E1 were confirmed in experiments with river water samples, in which E2 was converted into E1 and mineralised according to first order kinetics (Jürgens et al, 2002). The findings for the conversion of E2 to E1 were confirmed in experiments with river water samples, in which E2 was converted into E1 and mineralised according to first order kinetics (Jürgens et al, 2002).…”
Section: Activated Sludge Systemsmentioning
confidence: 58%
“…Regarding the fate of steroid hormones in the environment, these compounds are highly hydrophobic, low volatile and present low polarities with octanolwater partition coefficients (K ow ) ranging between 10 3 and 10 5 . Jürgens et al (2002) studied the behaviour of E2 and EE2 in surface waters. investigated the distribution of several estrogens between water column and sediments and they reported that they can be rapidly removed from Servos et al, 2005 4-7 France Cargouet et al, 2004 17b-estradiol (E2) 1-15 Canada Servos et al, 2005 5-9 France Cargouet et al, 2004 17-ethinylestradiol (EE2) 3-5 France Cargouet et al, 2004 water phase to sediments.…”
Section: Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Fate studies of estrogens in the environment show that some of them can persist for significant time in surface water. Jurgens et al (2002) reported that estradiol and estrone in stream water have half-lives of 0.1 and 11 days, respectively. This indicates that the persistence of these estrogens in surface water is due to ongoing release and not due to cumulative effect over a long term.…”
Section: Resultsmentioning
confidence: 99%
“…5) used for each of the selected estrogens are shown in Table 3 (derived from Jurgens et al [15]). The values of k 20 and (Eqn.…”
Section: Model Parameters For Steroid Estrogensmentioning
confidence: 99%